Kolektor energi surya dengan serbuk arang - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 1997)
ABSTRACT: Solar collectors with pulverized woodchar absorber has been investigated. The performance was compared to that of a commercial collector, Solahart. Two sizes of char particles, 0.5 mm and 1.0 mm, were used and the collector dimension was 100 x 50 x 15 cm. The results were promising. The absorber with small particles had an efficiency which is close to that of Solahart. The effects of particle sizes were also investigated. It was found that the absorber with small particles had better performance.